Treatment management of myoepithelial carcinoma of the palate: an integrative literature review (Research, Society and Development, 2021)
Myoepithelial carcinoma (MECA) accounts for only 0.1% of all salivary gland tumors, presenting aggressive behavior due to its infiltrative growth, including 37% of local recurrence and 22% of metastatic rate. So far, just over 28 cases of MECA involving minor salivary glands have been described in the literature, this number being even smaller when limited to the palate region. Therefore, the objective of this integrative literature review is to gather a series of clinical reports on the management of treatment applied to cases of myoepithelial carcinoma of the palate. The guiding question of the study was: “What is the treatment management for myoepithelial carcinoma in the palate?”. Searches were performed in PubMed/MEDLINE, Lilacs and SciELO databases until October 2021. A total of 11 studies published between 2021 and 1996 were included in this integrative review, totaling 14 patients diagnosed with MECA in the palate, 7 women and 7 men. The basic treatment management for myoepithelial carcinoma of the palate is wide excision surgery, with the choice of the professional and, depending on the degree of malignancy, the use of additional treatment, with a predilection for radiotherapy.